Intermediate filaments in alpha-keratins. - Fraser, R D (1986)
Previous x-ray diffraction studies on the alpha-keratins of hair and wool have revealed that the intermediate filaments (IF) have a helical structure rendered imperfect by a precisely defined dislocation. It has also been possible to deduce a surface lattice for the IF and to determine the number of IF molecules associated with each lattice point. In this work this information is combined with data on the ionic interactions between the coiled-coil rope segments of the IF molecules to provide a plausible model for the pattern of interactions that stabilize the framework of the IF in the "hard" alpha-keratins. Similar interaction studies of the proteins from the IF in the so-called "soft" alpha-keratin from the stratum corneum layer of the skin suggest that they are likely to have an essentially similar pattern.